The Domestication of the Amazon Tree Grape (Pourouma cecropiifolia) Under an Ecological Lens - Pedrosa, Hermísia C.; Clement, Charles R.; Schietti, Juliana (Frontiers in Plant Science, 2018)
Domestication studies traditionally focus on the differences in morphological characteristics between wild and domesticated populations that are under direct selection, the components of the domestication syndrome. Here, we consider that other aspects can be modified, because of the interdependence between plant characteristics and the forces of natural selection. We investigated the ongoing domestication of Pourouma cecropiifolia populations cultivated by Ticuna people in Western Amazonia, using traditional and ecological approaches. We compared fruit characteristics between wild and domesticated populations to quantify the direct effects of domestication. To examine the characteristics that are not under direct selection and the correlated effects of human selection and natural selection, we investigated the differences in vegetative characteristics, changes in seed:fruit allometric relations and the relations of these characteristics with variation in environmental conditions summarized in a Principal Component Analysis. Domestication generated great changes in fruit characteristics, as expected in fruit crops. The fruits of domesticated plants had 20x greater mass and twice as much edible pulp as wild fruits. The plant height:DBH ratio and wood density were, respectively, 42.15 % and 21.74 % smaller in domesticated populations, probably in response to greater luminosity and higher sand content of the cultivated landscapes. Seed:fruit allometry was modified by domestication: although domesticated plants have heavier seeds, the domesticated fruits have proportionally (46 %) smaller seed mass compared to wild fruits. The high light availability and poor soils of cultivated landscapes may have contributed to seed mass reduction, while human selection promoted seed mass increase in correlation with fruit mass increase. These contrasting effects generated a proportionately smaller increase in seed mass in domesticated plants. In this study, it was not possible to clearly dissociate the environmental effects from the domestication effects in changes in the morphological characteristics, because the environmental conditions were intensively modified by human management. The plant domestication is intrinsically related to the landscape domestication. Our results suggest that evaluation of environmental conditions together with human selection on domesticated phenotypes provide a better understanding of the changes generated by domestication in plants.